2000
DOI: 10.1111/j.1572-0241.2000.03254.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral pantoprazole for erosive esophagitis: a placebo-controlled, randomized clinical trial

Abstract: Pantoprazole was safe and effective for healing erosive esophagitis and provided rapid symptomatic relief. These results indicate that pantoprazole offers a new option for treatment of erosive esophagitis. Among the three doses studied, the 40-mg dose was the most effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(67 citation statements)
references
References 14 publications
5
59
0
2
Order By: Relevance
“…The efficacy of PPIs in the management of nighttime heartburn has been documented in placebo-controlled studies [20, 21]. In the US Gallup survey, satisfaction with prescription medication was markedly higher than with over-the-counter medication or with lifestyle changes such as avoiding meals before going to bed or elevating the head of the bed [7].…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of PPIs in the management of nighttime heartburn has been documented in placebo-controlled studies [20, 21]. In the US Gallup survey, satisfaction with prescription medication was markedly higher than with over-the-counter medication or with lifestyle changes such as avoiding meals before going to bed or elevating the head of the bed [7].…”
Section: Discussionmentioning
confidence: 99%
“…Proton pump inhibitor (PPI) is the most effective treatment of GERD [12,13,14]. Daily PPI therapy results in healing of about 80% of moderate-to-severe reflux oesophagitis [15,16,17]. GERD is less prevalent in Asian countries and the perception is that Asians tend to have a milder spectrum of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies [20,21,22,23,24] show that 88–96% of patients with reflux esophagitis present with normal endoscopic findings after 8 weeks of therapy with standard dose PPIs, regardless of the brand of PPIs and the severity of mucosal damage. Carlsson et al [9] also showed that approximately 27% of 225 patients with reflux esophagitis continue to experience heartburn, despite complete mucosal healing.…”
Section: Epidemiologymentioning
confidence: 99%